The admission of Asian patients to intensive therapy units and its implications for kidney donation: a preliminary report from Coventry, UK. Issue 4 (August 1996) - Exley, C; Sim, J; Reid, N G; Booth, L; Jackson, S; West, N
Abstract : OBJECTIVE: To determine the relative admission rates of Asian and non-Asian patients to intensive therapy units (ITUs) in Coventry and to explore the implications of these rates for the transplantation of organs to Asian people. DESIGN: Examination of 1991 census data and a retrospective review of ITU admissions books. Data were collected on ethnic background, presenting diagnosis, and clinical outcome for each admission. SETTING: The three ITUs in Coventry. PATIENTS: All admissions to the ITUs from 1990-93 inclusive. RESULTS: Asian patients were admitted to ITUs disproportionately to their numbers in the Coventry population. Members of the Asian community were less than half as likely to be admitted to an ITU (p < 0.001) and more likely to die while there (p = 0.007) than members of the non-Asian population in Coventry. The proportions of patients referred to the transplant unit and the rates of subsequent donation do not seem to differ significantly for Asian and non-Asian patients (p = 0.26 in both cases). CONCLUSIONS: There are clear implications for the availability of cadaveric kidney transplantation to Asian patients, given that few kidneys from non-Asian donors are histocompatible with Asian recipients. Indeed, in Asians, promotion of living related donation may be more effective in countering the organ shortfall than efforts to increase consent to cadaveric transplantation. However, it may be valuable to investigate any patterns of morbidity or social or cultural factors that might explain the initial low admissions rates to ITUs for Asian patients.